Cytoskeletal control of the secretory immune synapse - Douanne, Tiphaine; Griffiths, Gillian M. (Current opinion in cell biology, 2021)
The immune synapse is a very important but often transient site for secretion between immune cells. How secretion is controlled in a coordinated fashion at the synapse is a subject of much investigation. Two key mechanisms are the polarisation of the centrosome and rapid actin dynamics across the immune synapses that form between interacting immune cells. In recent years it has become clear that different immune cells utilise a diversity of immune synapses that modify these mechanisms in order to optimise specialised modes of secretion. Here we describe some of the latest research, focusing on regulation by centrosomal and actin dynamics in a variety of immune cells.